PENGEMBANGAN MEDIA TIGA DIMENSI UNTUK MENINGKATKAN LIFE SKILLS MAHASISWA PENDIDIKAN SEJARAH IKIP PGRI MADIUN - Hanif, Muhammad (Jurnal Pendidikan, 2008)
One out of some objectivesÂ of carryingÂ out the scholarshipÂ of the History StudyÂ ProgramÂ of IKIPÂ Â PGRI MadiunÂ is to enhance:Â (1) teachersÂ who have sufficientÂ competenceÂ Â in their teachingÂ skill, (2) teachersÂ who are sensitiveÂ towardsÂ the progressÂ of the history and all social process within the society, 3) teachersÂ who are flexibleÂ against the developmentÂ Â of historyÂ of IndonesiaÂ Â Â byÂ havingÂ the historical awarenessÂ as front-linersÂ of educationalÂ Â conducts.Â The competence copesÂ with competenceÂ Â and qualificationÂ Â at the cognitive,Â affective and psychomotorÂ domains.Â Such a competenceÂ Â leads the learnersÂ to life-skillÂ Â Â thatÂ Â studentsÂ shouldÂ Â copeÂ Â with.Â AmongÂ Â someÂ Â ways developingÂ the lecturers competenceÂ at the three domainsÂ mentioned aboveÂ in generatingÂ Â the, studentsÂ Â life-skill,Â Â itÂ isÂ suggestibleÂ Â that lecturers developÂ teachingÂ method. Three-dimensionÂ Â teachingÂ media is oneÂ methodÂ thatÂ is presumptivelyÂ Â ableÂ to developÂ the lecturersÂ competenceÂ in generatingÂ the studentsÂ life-skill. This research serves an analysis on the significanceÂ of the use of three-dimensionÂ teaching mediaÂ onÂ theÂ studentsâ life skill.Â ThisÂ research,Â Â then,Â proposes objectivesÂ as to identify the significanceÂ of three-dimensionÂ Â teaching media towardsÂ the studentsÂ life-skill.The researchÂ methodÂ appliedÂ in this researchÂ is ResearchÂ and DevelopmentÂ coping with three stages, i.e.: (1) explorationÂ under qualitativeÂ descriptiveÂ method, (2) developmentÂ under single one shot case study, (3) experimentationÂ Â method. The subjects of the study are all of the students of the History Study Program of IKIP PGRI Madiun.The research lasts in drawing conclusionÂ that the development of three-dimensionÂ Â teachingÂ media can analyticallyÂ improve life skill of the students of History Study Program of IKIP PGRI Madiun. Then the hypothetic model as shown in figure 1 is attested already as it is shown in figure 2 and 3 under attested consistence and validity in generating the life-skill of the students of History Program of IKIP PGRI Madiun.Key terms: three-dimension teaching media, life-skill